Effect of granular activated carbon and other porous materials on thermal decomposition of per- and polyfluoroalkyl substances: Mechanisms and implications for water purification. (15th July 2021) - Sasi, Pavankumar Challa; Alinezhad, Ali; Yao, Bin; Kubátová, Alena; Golovko, Svetlana A.; Golovko, Mikhail Y.; Xiao, Feng
Highlights: A study on thermal decomposition of PFAS and GenX that has been poorly understood. The decomposition involves initiation, chain propagation, and termination reactions. Dual thermal decomposition pathways of PFAS seem to exist. GAC dramatically altered the thermal decomposition rate and pathway of PFCAs. Raw, non-activated charcoals/biochars had little effect on this process. Abstract: Thermal treatment is routinely used to reactivate the spent granular activated carbon (GAC) from water purification facilities. It is also an integral part of sewage sludge treatment and municipal solid waste management. This study presents a detailed investigation of the fate of per- and polyfluoroalkyl substances (PFAS) and one PFAS alternative (GenX) in thermal processes, focusing on the effect of GAC. We demonstrate that the thermolysis of perfluoroalkyl carboxylic acids (PFCAs), including perfluorooctanoic acid (PFOA), and GenX can occur at temperatures of 150‒200 °C. Three temperature zones were discovered for PFOA, including a stable and nonvolatile zone (≤90 °C), a phase-transfer and thermal decomposition zone (90‒400 °C), and a fast decomposition zone (≥400 °C). The thermal decomposition began with the homolysis of a C‒C bond next to the carboxyl group of PFCAs, which formed unstable perfluoroalkyl radicals. Dual decomposition pathways seem to exist. The addition of a highly porous adsorbent, such as GAC or a copolymer resin, compressed the intermediate sublimation zone of PFCAs, changed their thermal decomposition pathways, and increased the decomposition rate constant by up to 150-fold at 250 °C. The results indicate that the observed thermal decomposition acceleration was linked to the adsorption of gas-phase PFCA molecules on GAC. The presence of non-activated charcoals/biochars with a low affinity for PFOA did not accelerate its thermal decomposition, suggesting that the π electron-rich, polyaromatic surface of charcoal/GAC played an insignificant role compared to the adsorbent's porosity. Overall, the results indicate that (1) substantial decomposition of PFCAs and GenX during conventional thermal GAC/sludge/waste treatment is very likely, and (2) the presence or addition of GAC or other highly porous materials can accelerate thermal PFAS decomposition and alter decomposition pathways.